5-Acetyl goniothalamin, a styryl dihydropyrone from Goniothalamus uvaroides - Badruddin Ahmad, Fasihuddin; Tukol, Wan Ahmad; Omar, Siraj; Mohd. Sharif, Atan (Pergamon Press, 1991)
Two major compounds have been isolated and characterized from the roots of Goniothalamus uvaroides: goniothalamin, a biologically active styryl dihydropyrone, and its derivative, 5-acetyl goniothalamin. The isolation of goniothalamin has been previously reported from several Goniothalamus species collected from Peninsular Malaysia, Sabah and Sarawak. However, 5-acetyl goniothalamin has never been reported before. Structure elucidation of these compounds was carried out by spectroscopic methods. © 1991.